2016
DOI: 10.3390/s16020160
|View full text |Cite
|
Sign up to set email alerts
|

A Full Parallel Event Driven Readout Technique for Area Array SPAD FLIM Image Sensors

Abstract: This paper presents a full parallel event driven readout method which is implemented in an area array single-photon avalanche diode (SPAD) image sensor for high-speed fluorescence lifetime imaging microscopy (FLIM). The sensor only records and reads out effective time and position information by adopting full parallel event driven readout method, aiming at reducing the amount of data. The image sensor includes four 8 × 8 pixel arrays. In each array, four time-to-digital converters (TDCs) are used to quantize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…74 In the last decades, arrays of SPADs with integrated TDCs have been developed. 63,[75][76][77][78][79][80][81] The number of pixels for typical devices is 32 Â 32 or 64 Â 64, with the time channel width of the TDCs in the range of 50 ps to 120 ps. A device with 252 Â 144 pixels shared 1728 TDCs has recently been developed by Lindner et al 82 Henderson et al have reported a 192 Â 128 SPAD array with TDCs in every pixel.…”
Section: Wide-¯eld Tcspc-flim With Spad Arraysmentioning
confidence: 99%
“…74 In the last decades, arrays of SPADs with integrated TDCs have been developed. 63,[75][76][77][78][79][80][81] The number of pixels for typical devices is 32 Â 32 or 64 Â 64, with the time channel width of the TDCs in the range of 50 ps to 120 ps. A device with 252 Â 144 pixels shared 1728 TDCs has recently been developed by Lindner et al 82 Henderson et al have reported a 192 Â 128 SPAD array with TDCs in every pixel.…”
Section: Wide-¯eld Tcspc-flim With Spad Arraysmentioning
confidence: 99%
“…This is even more true for A-SPADs, since meaningful angular information (which is derived from diffraction, and so the wave-description of light) can only be extracted by measuring the average of discrete photon detection events (derived from the particle description of light) [ 22 ]. On-chip data compression or decimation may partly resolve this issue (event-driven readout [ 30 ], embedded FIFO [ 31 ]), but still suffers from inefficiencies due to moving inherently redundant data from the array core to the compression circuitry [ 24 ]. For the A-SPAD array, described here, which operates in a low figure environment while collecting extra dimensions of information, we took the simple yet efficient alternative approach of pixel level averaging combined with tightly controlled detection windows.…”
Section: Angle-sensitive Single Photon Avalanche Diodementioning
confidence: 99%
“…The role of a TDC is to measure precise time intervals between two events represented by two signals (reference and measured signals) [1][2][3][4], which is the keystone of many applications such as LIDAR applications [5], time-resolved fluorescence measurement [6], fluorescence lifetime imaging [7], 3-D active imaging and time-correlated photon counting [8]. In general, high-resolution TDCs can be built as Application-Specific Integrated Circuits (ASICs) [9].…”
Section: Introductionmentioning
confidence: 99%